Evolution of Egyptian religion reflected in temple architecture - Barnes, Nicole Marie (My University, 2012)
Religion was vital to Ancient Egyptian life; even foreign rule could not change the Egyptians' need to express their conviction in their deep rooted religious beliefs. By looking at Egyptian divine temples from the New Kingdom to the Graeco-Roman era (~1550 B.C. ? A.D. 395), you can see that architecture and decoration alterations in response to changes in the current practicing religion making it possible to determine during which time period some features were constructed. This study will look at changes in religion to determine identifiable characteristics that should appear in the temple design and decoration. The research will conclude that the presence of mammisis (birth houses), Serapis, extensive animal mummification, and temples dedicated to a goddess are reliable characteristics that may help to date a temple that was constructed during the Graeco-Roman period.
Keywords: Egypt -- Civilization.; Architecture, Egyptian -- History.; Architecture -- Designs and plans.